Genomic and transcriptomic analyses provide insights into valuable fatty acid biosynthesis and environmental adaptation of yellowhorn - Liang, Qiang; Liu, Jian Ning; Fang, Hongcheng; Dong, Yuhui; Wang, Changxi; Bao, Yan; Hou, Wenrui; Zhou, Rui; Ma, Xinmei; Gai, Shasha; Wang, Lichang; Li, Shouke; et al. (Frontiers in Plant Science, 2022)
Yellowhorn (Xanthoceras sorbifolium) is an oil-bearing tree species growing naturally in poor soil. The kernel of yellowhorn contains valuable fatty acids like nervonic acid. However, the genetic basis underlying the biosynthesis of valued fatty acids and adaptation to harsh environments is mainly unexplored in yellowhorn. Here, we presented a haplotype-resolved chromosome-scale genome assembly of yellowhorn with the size of 490.44 Mb containing scaffold N50 of 34.27 Mb. Comparative genomics, in combination with transcriptome profiling analyses, showed that expansion of gene families like long-chain acyl-CoA synthetase and ankyrins contribute to yellowhorn fatty acid biosynthesis and defense against abiotic stresses, respectively. By integrating genomic and transcriptomic data of yellowhorn, we found that the transcription of 3-ketoacyl-CoA synthase gene XS04G00959 was consistent with the accumulation of nervonic and erucic acid biosynthesis, suggesting its critical regulatory roles in their biosynthesis. Collectively, these results enhance our understanding of the genetic basis underlying the biosynthesis of valuable fatty acids and adaptation to harsh environments in yellowhorn and provide foundations for its genetic improvement.